Halide-driven polymorph selectivity in the synthesis of MnX (X = S, Se) nanoparticles. Issue 6 (25th January 2023) - Gendler, Danielle; Bi, Jiaying; Mekan, Deep; Warokomski, Ashley; Armstrong, Cameron; Hernandez-Pagan, Emil A.
Abstract : Polymorph selectivity controlled by halide precursor. Abstract : Devising synthetic strategies to control crystal structure is of great importance as materials properties are governed by structure. MnS is a great model system as it has three known stable polymorphs. Herein, we show the selective synthesis of colloidal wurtzite- and rock-salt-type MnS under identical reactions conditions changing only the manganese halide precursor. Mixtures of Mn halides or halide surrogate ( e.g., NH4 Cl) also enabled polymorph control. Powder X-ray diffraction aliquot studies of the reactions revealed the crystal structure at the onset of nucleation and that of the final product is the same, unlike the Ostwald ripening transformation observed in other systems. The halide-driven selectivity was also observed in the synthesis of manganese selenide nanoparticles. In this system, variation of the Mn halide precursor allowed access to the wurtzite- and rock salt-type polymorphs of MnSe, as well as the pyrite-MnSe2 phase. Based on this work, the mixing of metal salts might be a simple and effective strategy towards polymorph control and access materials with new crystal structures.